Sistem Pakar Mendiagnosa Penyakit Itp (Idiopathic Thormbocytopenict Purpura) Mengunakan Metode Variable Centered Intelligent Rule System (VCIRS) - Mhd. Iskandar Romadon Hasibuan (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
At this time the use of computer peripheral technology has grown rapidly and is popular in the community. Most people use it not only for commercial purposes, but also to obtain information on the detection of disease quickly and efficiently with computer-based applications that can help the general public to find out the causes and symptoms of these diseases. For this reason, we need a system designed to be able to mimic the expertise of an expert in answering questions and solving a problem in accordance with the knowledge of an expert entered into a computer system. The development of Artificial Intelligence technology that has occurred has enabled the Expert System to be applied in detecting diseases using the programming language. One of them is in providing information about various problems, especially ITP (Idiopathic Thrombocytopenic Purpura) disease. The expert system method used is the Variable Centered Intelligent Rule System (VCIRS) used to deal with diagnosing ITP disease. With the facilities provided for users and administrators, it allows both users and administrators to use this system according to their individual needs. Users are given the ease of knowing information about ITP disease, its causes and prevention. This Expert System was created using the Microsoft Visual Basic 2008 Programming Language.